Fortified Settlements in the Eastern Baltic: From Earlier Research to New Interpretations - Lang, Valter (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian] A brief history of research and earlier interpretations of fortified settlements east of the Baltic Sea are provided in the first part of the article. The earlier research has resulted in the identification of the main area of the distribution of fortified settlements, the main chronology in the Late Bronze and Pre-Roman Iron Ages, and their general cultural and economic character. It has been thought that the need for protection – either because of outside danger or social tensions in society – was the main reason for the foundation of fortified sites. The second part of the article adds a new possibility of interpreting the phenomenon of fortified settlements, proceeding from ethnogenesis of the Finnic and Baltic peoples. It is argued that new material culture forms that took shape in the Late Bronze Age – including fortified settlements and find assemblages characteristic of them – derived at least partly from a new population arriving in several waves from the East-European Forest Belt.